Hot melt adhesives and color changing hot melt adhesives
A hot-melt adhesive with a block copolymer and tackifiers addresses misalignment and adhesion issues, ensuring durable bonding and visual confirmation of activation across temperature extremes, improving work efficiency and safety.
Patent Information
- Application Number
- JP2022147101
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-10-15
- Filing Date
- 2022-09-15
- Publication Date
- 2025-01-17
- Estimated Expiration
- 2042-09-15
AI Technical Summary
Existing adhesives for bonding road marking materials and guidance panels face issues with misalignment due to flexibility, inadequate heat transfer, and adhesion failure in varying temperatures, requiring special equipment and posing environmental and safety risks.
A hot-melt adhesive using a block copolymer of alkyl methacrylate and alkyl acrylate with specific tackifiers and plasticizers, ensuring a softening point of 90°C or higher, which allows for visual confirmation of activation and improved adhesion across temperature extremes.
The adhesive provides durable bonding that resists peeling and shifting under vehicle traffic, ensures effective adhesion in extreme temperatures, and allows visual confirmation of activation, enhancing work efficiency and safety.
Smart Images

Figure 0007616180000001 
Figure 0007616180000002 
Figure 0007616180000003
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot melt adhesive. More specifically, the present invention relates to a hot melt adhesive that can be applied in a hot molten or heat softened state, and that can be heated and melted on a road surface when in use, i.e., when applied, and then bonded to a road marking material or an induction panel. Furthermore, the present invention relates to an adhesive sheet made using the hot melt adhesive. [Background technology]
[0002] Display materials and guide panels for warnings and direction guidance are often attached to roads, sidewalks, floors of buildings and factories, train platforms, etc. Proposed methods of attachment include a pressure-sensitive adhesive sheet type in which an adhesive layer is laminated on a substrate (Patent Document 1), a hot melt type in which a laminate in which a hot melt adhesive is laminated on a substrate is heated from the side where the hot melt adhesive is not applied to bond them together (Patent Document 2), and a curing adhesive that uses a base agent and a curing agent (Patent Document 3). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Japanese Patent Application Publication No. 6-280221 [Patent Document 2] JP 2001-26915 A [Patent Document 3] JP2012-97561A Summary of the Invention [Problem to be solved by the invention]
[0004] When used on outdoor roads, weather-resistant marking materials and guide panels made of polymethyl methacrylate, polyvinyl chloride, etc. are used. Adhesives that can bond road marking materials and guide panels together must have excellent adhesive strength for these materials and be durable enough not to peel off or shift even when vehicles pass, brake, or change direction in all-year-round environments, from cold winters to hot summers.
[0005] However, the pressure-sensitive adhesive sheet type of Patent Document 1 uses an adhesive layer that is too flexible, so after it is attached to the road surface, when a vehicle brakes or changes direction while passing over it, it shifts, causing the panel to fail to accurately function as a guide panel. In addition, in Patent Document 2, the road marking material is heated from the other side where the hot melt adhesive is not applied, and adhesion is easy when the marking material is 0.3 mm thick because heat is immediately transferred to the hot melt, but when the marking material is 2 mm thick and the hot melt adhesive is 1 mm thick, it is difficult to uniformly melt the entire hot melt adhesive surface that is in contact with the road surface and bond it, and many of the base materials are not transparent, so the adhesive state cannot be confirmed visually. Furthermore, in winter, when the road surface is below zero, heat is very difficult to transfer, and there is a problem that adhesion failure is very likely to occur. On the other hand, Patent Document 3 is a curing type adhesive that is bonded by mixing the base agent and hardener, but in order to mix the base agent and hardener, a dedicated device such as a mixer is required, and since it takes time to harden after application, the work efficiency is poor. In addition, since acrylic syrup containing a large amount of flammable acrylic monomer is hardened by radical polymerization, there are problems in terms of the environment (odor, health) and safety (reaction control, risk of fire).
[0006] The present invention aims to provide a hot melt adhesive that can be used to attach road surface marking materials or guide panels to road surfaces such as asphalt or concrete, that can be confirmed to have been sufficiently heated and activated by the disappearance of its color when attached by heating, and that is unlikely to cause poor adhesion due to insufficient heating. Another aim of the present invention is to provide an attachment structure that, after attachment, does not peel off or shift when a vehicle passes, brakes, or changes direction, even at high summer temperatures or low winter temperatures. [Means for solving the problem]
[0007] Means for Solving the Problems The present inventors conducted intensive research to solve the above problems, and as a result, discovered a hot melt adhesive that can solve the problems by using a tackifier having a softening point of 130°C or more and a tackifier having a softening point of less than 130°C for a block copolymer of an alkyl methacrylate ester and an alkyl acrylate ester.
[0008] That is, the present invention relates to the following [1] to [6]. [1] A block copolymer (A) including a polymer block containing a structural unit derived from an alkyl methacrylate ester having an alkyl group with 1 to 3 carbon atoms and a polymer block containing a structural unit derived from an alkyl acrylate ester having 1 to 8 carbon atoms in the alkyl group; a tackifier (B) having a softening point of 130°C or more; and a tackifier (C) having a softening point of less than 130°C; A hot melt adhesive for attaching road surface marking materials, having a softening point of 90°C or higher, which contains 40 to 70 mass% of block copolymer (A) and 5 to 45 mass% of tackifier (B) out of a total of 100 mass% of (A), (B), and (C), and the total of tackifier (B) and tackifier (C) is 30 to 60 mass%.
[0009] [2] The hot melt adhesive for attaching road surface marking materials according to [1], further comprising a plasticizer (D) that is liquid at 23°C.
[0010] [3] A hot melt adhesive for attaching road surface marking materials according to [1] or [2], further comprising a synthetic wax (G).
[0011] [4] The hot melt adhesive for attaching road surface marking materials according to any one of [1] to [3], wherein the mass ratio of the methacrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms in the block polymer (A) is 10 to 55 mass %.
[0012] [5] A hot melt adhesive for attaching road surface marking materials according to any one of [1] to [4], wherein the block copolymer (A) comprises at least one of a block copolymer of methyl methacrylate and n-butyl acrylate, a block copolymer of methyl methacrylate and 2-ethylhexyl acrylate, and a copolymer of methyl methacrylate, n-butyl acrylate, and 2-ethylhexyl acrylate.
[0013] [6] A color-changing hot-melt adhesive for attaching road surface marking materials, further comprising 0.003 to 3 mass% of a color developer (E) based on 100 mass% of the hot-melt adhesive for attaching road surface marking materials described in any one of [1] to [5], and satisfying the following (1) or (2). (1) The sum of the acid values of (A), (B), (C), and (D) is 0.8 mg KOH / g or more. (2) It further contains an acidic substance (F), and the sum of the acid values of (A), (B), (C), (D) and (F) is 0.8 mg KOH / g or more. Effect of the Invention
[0014] The present invention has made it possible to provide a hot melt adhesive that can safely bond road surface marking materials and guide panels to road surfaces such as asphalt and concrete, that can confirm that the adhesive has been sufficiently heated and activated when bonded by heating even under low temperature outdoor conditions in winter by the disappearance of its color, and that is less likely to cause poor adhesion due to insufficient heating.The present invention also makes it possible to provide an attachment structure that, after bonding, does not peel off or shift when a vehicle passes, brakes, or changes direction, even under high temperatures in summer or low temperatures in winter. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] In this specification, any numerical range specified using "to" is intended to include the numerical values before and after "to" as the lower and upper limit values of the range.
[0016] <Block copolymer (A)> The block copolymer (A) contained in the hot melt adhesive of the present invention is a block copolymer of a polymer block containing a structural unit derived from an alkyl methacrylate ester having an alkyl group with 1 to 3 carbon atoms, and a polymer block containing a structural unit derived from an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms. Examples of the block copolymer (A) include a triblock polymer in which a hard segment (AS) formed from an alkyl methacrylate having an alkyl group with a carbon number of 1 to 3 and a soft segment (AH) formed from an alkyl acrylate having an alkyl group with a carbon number of 1 to 8 are bonded as -AS-AH-AS-, and a diblock polymer in which they are bonded as -AS-AH-. A triblock polymer and a diblock polymer may be used in combination.
[0017] Since the block copolymer (A) is clearly divided into a polymer portion (hard segment) of an alkyl methacrylate ester having an alkyl group with 1 to 3 carbon atoms and a polymer portion (soft segment) of an alkyl acrylate ester having 1 to 8 carbon atoms, it is possible to obtain a hot melt adhesive that has both heat-resistant adhesive strength and low-temperature adhesive strength by utilizing each polymer portion (segment). The hard segment can increase the cohesive strength of the hot melt adhesive, and by using a tackifier (B) (C) or a plasticizer (D) described later in combination, it is possible to impart wettability and adhesive strength to the adherend to the soft segment.
[0018] Examples of the methacrylic acid alkyl ester having an alkyl group having 1 to 3 carbon atoms for forming the hard segment of the block copolymer (A) include methyl methacrylate, ethyl methacrylate, n-propyl methacrylate, and isopropyl methacrylate. From the viewpoint of increasing the cohesive strength at 60°C required to achieve the 60°C adhesive strength, methyl methacrylate is preferred.
[0019] Examples of alkyl acrylates having an alkyl group with 1 to 8 carbon atoms for forming the soft segment of the block copolymer (A) include methyl acrylate, ethyl acrylate, n-propyl acrylate, isopropyl acrylate, n-butyl acrylate, isobutyl acrylate, isoamyl acrylate, hexyl acrylate, octyl acrylate, and 2-ethylhexyl acrylate. From the viewpoint of easily achieving both 60°C adhesive strength and -10°C adhesive strength, n-butyl acrylate, 2-ethylhexyl acrylate, or a combination of these is preferred.
[0020] The mass ratio of the methacrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms in the block polymer (A) is preferably 10 to 55 mass%. Since the acrylic acid alkyl ester has a lower glass transition temperature than methyl methacrylate, is easy to flow, and is also easily compatible with tackifiers, the lower the ratio of the methacrylic acid alkyl ester and the higher the ratio of the acrylic acid alkyl ester, the easier it becomes to wet the interface of the adherend and the higher the adhesive strength becomes. By being within the above range, both the performance of the 60°C adhesive strength and the workability of heat dissolution can be achieved. Furthermore, the mass ratio of the methacrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms is more preferably 10 to 40 mass%.
[0021] Examples of the block copolymer (A) include KURARITY LA2140E (MMA-BA / triblock copolymer, mass ratio of MMA: 20% by mass), KURARITY LA2250 (MMA-BA / triblock copolymer, mass ratio of MMA: 30% by mass), KURARITY LA2330 (MMA-BA / triblock copolymer, mass ratio of MMA: 20% by mass), KURARITY LA3320 (MMA-BA / triblock copolymer, mass ratio of MMA: 15% by mass), KURARITY LA3170 (MMA-BA / triblock copolymer, mass ratio of MMA: 12% by mass), KURARITY LA2270 (MMA-BA / triblock copolymer, mass ratio of MMA: 40% by mass), KURARITY LA4 285 (MMA-BA / triblock copolymer, mass ratio of MMA: 50% by mass), Clarity LA1892 (MMA-BA / triblock copolymer, mass ratio of MMA: 52% by mass), Clarity LK9243 (MMA-(BA-2EHA) / triblock copolymer, MMA ratio: 17% by mass), Clarity KL-LK9333 (MMA(BA-2EHA) / triblock copolymer, MMA ratio: 20% by mass) or more, manufactured by Kuraray Co., Ltd., and the like can be mentioned, and each can be used alone or in combination. Furthermore, from the viewpoint of initial adhesion, Clarity LA140E, Clarity LA2250, Clarity LA2330, Clarity LA3320, Clarity LA3170, Clarity LA2270, Clarity LK9243 and Clarity LK9333 are preferred.
[0022] The block copolymer (A) is contained in an amount of 40 to 70% by mass, more preferably 45 to 65% by mass, of the total of (A) to (C) being 100% by mass. If it is less than 40% by mass, the adhesive strength at -10°C decreases and the material becomes easily peeled off, whereas if it exceeds 70% by mass, the heat melting property decreases and workability becomes poor. <Tackifier (B)> As the tackifier (B), any of the following can be used so long as it has a softening point of 130° C. or higher: phenolic resin, modified phenolic resin, terpene resin, terpene phenolic resin, xylene phenolic resin, xylene resin, α-methylstyrene resin, cyclopentadiene-phenolic resin, aliphatic and aromatic petroleum resins, phenol-modified petroleum resin, rosin ester, polymerized rosin, hydrogenated rosin ester and polymerized rosin, low molecular weight polystyrene resin, terpene resin, hydrogenated aliphatic and aromatic petroleum resins, etc. The upper limit of the softening point is not particularly limited as long as it is within a practical range, but if it is forced to be set, it is 160° C. The softening point is a value measured in accordance with the softening point measuring method according to JIS K2207, ring and ball method.
[0023] The tackifier (B) is contained in an amount of 5 to 45% by mass, more preferably 10 to 40% by mass, out of the total of (A) to (C) being 100% by mass. If it is less than 5% by mass, the adhesive strength at 60°C will be low, and if it exceeds 45% by mass, the adhesive strength at -10°C will be low.
[0024] <Tackifier (C)> As the tackifier (C), any of the following can be used so long as it has a softening point of less than 130° C.: phenolic resin, modified phenolic resin, terpene resin, terpene phenolic resin, xylene phenolic resin, xylene resin, α-methylstyrene resin, cyclopentadiene-phenolic resin, aliphatic and aromatic petroleum resins, phenol-modified petroleum resin, rosin ester, polymerized rosin, hydrogenated rosin ester and polymerized rosin, low molecular weight polystyrene resin, terpene resin, hydrogenated aliphatic and aromatic petroleum resins, etc. The lower limit of the softening point is not particularly limited as long as it is within a practical range, but if forced to be set, it is 70° C.
[0025] Of the total of (A) to (C) being 100% by mass, the total of tackifier (B) and tackifier (C) is 30% to 60% by mass, more preferably 35% to 55% by mass. If the total of tackifier (B) and tackifier (C) is less than 30% by mass, the 60°C adhesive strength will be low, and if it exceeds 60% by mass, the -10°C adhesive strength will be low.
[0026] <Hot melt adhesive for attaching road marking materials> The hot melt adhesive for attaching road surface marking materials of the present invention can be produced by mixing, by a known method, the block copolymer (A) of the methacrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms and the acrylic acid alkyl ester having an alkyl group with 1 to 8 carbon atoms, the tackifier (B) having a softening point of 130° C. or more, and the tackifier (C) having a softening point of less than 130° C. The production method is not particularly limited, and examples thereof include a method of heating and mixing using a roll, a Banbury mixer, a kneader, or a melting kettle equipped with a stirrer.
[0027] The hot melt adhesive for attaching road surface marking materials of the present invention has a softening point of 90° C. or higher. The upper limit of the softening point is not particularly limited as long as it is within a practical range, but if it is forced to be set, it is 150° C. By having a softening point of 90° C. or higher, it is possible to improve the 60° C. adhesive strength. The softening point is measured in accordance with JIS K6863-1994, and details are given in the Examples section.
[0028] The hot melt adhesive for attaching road surface marking materials of the present invention may contain a plasticizer (D), a synthetic wax (G), additives, etc., within the scope of the invention.
[0029] As the plasticizer (D), any one can be used so long as it is liquid at 23°C, including phthalate esters, isophthalate esters, terephthalate esters, adipate esters, trimellitate esters, pyromellitate esters, cyclohexene dicarboxylate esters, ricinoleate esters, polyesters, acetate esters, phosphate esters, citrate esters, epoxidized vegetable oils, sebacate esters, azelaic acid esters, maleate esters, benzoate esters, polyether esters, glycerin fatty acid esters, polyglycerin fatty acid esters, sorbitan fatty acid esters, propylene glycol fatty acid esters, and acrylic polymer oligomers. When the plasticizer (D) is blended, the amount of the plasticizer (D) is preferably 1 to 30% by mass relative to 100% by mass of the total of the (A) to (C). In this range, both heat resistance and low temperature properties can be achieved, and the melt viscosity can be reduced, improving the heat melting property. 1 to 25% by mass is more preferable.
[0030] The hot melt adhesive for attaching road surface marking materials of the present invention may further contain a synthetic wax (G) for the purpose of improving heat solubility and adhesive strength at 60° C., within the scope of the invention without impairing the object of the invention. Examples of the synthetic wax (G) include fatty acid amide compounds, alkylene fatty acid amide compounds, and fatty acid ester compounds.
[0031] Examples of fatty acid amide-based synthetic waxes include: aliphatic monocarboxylic acid amides such as lauric acid amide, palmitic acid amide, oleic acid amide, stearic acid amide, erucic acid amide, behenic acid amide, ricinoleic acid amide, and hydroxystearic acid amide; Examples of the amides include N-substituted aliphatic monocarboxylic acid amides such as N-oleyl oleic acid amide, N-oleyl stearic acid amide, N-stearyl oleic acid amide, and N-hydroxyethyl-12-hydroxystearic acid amide.
[0032] Examples of synthetic waxes based on bis-fatty acid amide include alkylene aliphatic monocarboxylic acid amides such as methylene bis-stearic acid amide and ethylene bis-stearic acid amide; Examples of the amides include N,N'-substituted aliphatic monocarboxylic acid amides such as N,N'-ethylene-bis-oleylamide, N,N'-ethylenebisstearic acid amide, N,N'-ethylene-bis-hydroxystearic acid amide, N,N'-hexamethylene-bis-12-hydroxystearic acid amide, N,N'-methylenebisstearic acid amide, and N,N'-xylylene-bis-12-hydroxystearic acid amide.
[0033] Fatty acid ester-based synthetic waxes are those in which one or more fatty acids are ester-bonded to an alcohol, and examples of such waxes include glycerin fatty acid esters.
[0034] Examples of glycerol fatty acid esters include stearic acid monoglyceride, stearic acid monodiglyceride, behenic acid monoglyceride, behenic acid monodiglyceride, caprylic acid monodiglyceride, caprylic acid triglyceride, glycerol mono 12-hydroxystearate, oleic acid monoglyceride, oleic acid monodiglyceride, lauric acid monoglyceride, lauric acid monodiglyceride, stearic acid oleic acid monoglyceride, stearic acid oleic acid monodiglyceride, succinic acid fatty acid monoglyceride, citric acid fatty acid monoglyceride, diacetyltartaric acid fatty acid monoglyceride, diglycerol monomyristate, tetraglycerol stearate, decaglycerol laurate, decaglycerol stearate, decaglycerol oleate, and polyglycerol polyricinoleate. The term "·· acid monodiglyceride" refers to a composition containing "·· acid monoglyceride" and "·· acid diglyceride." Among these, stearic acid monoglyceride, stearic acid monodiglyceride, behenic acid monoglyceride, behenic acid monodiglyceride, glycerin mono 12-hydroxystearate, succinic acid fatty acid monoglyceride, and citric acid fatty acid monoglyceride are preferred, as they have melting points of 60° C. or higher and therefore are less likely to cause a decrease in viscosity as well as a decrease in heat resistance.
[0035] These synthetic waxes may be used alone or in combination of two or more kinds. When the synthetic wax (G) is blended, the synthetic wax (G) is preferably 1 to 25% by mass relative to 100% by mass of the total of (A) to (D). By being in this range, it is possible to improve heat resistance while maintaining low temperature properties, and further reduce melt viscosity, thereby improving heat melting properties. 1 to 20% by mass is more preferable.
[0036] Additives that may be blended into the hot melt adhesive for attaching road surface marking materials of the present invention within limits that do not impair the object of the invention include antioxidants, ultraviolet absorbers, light stabilizers, antibacterial agents, deodorants, and fragrances.
[0037] Examples of the antioxidant include pentaerythritol tetrakis[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate], octadecyl-3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate, diethyl [[3,5-bis(1,1-dimethylethyl)-4-hydroxyphenyl]methyl]phosphonate, 4,6-bis(octylthiomethyl)-o-cresol, ethylene bis(oxyethylene) bis[3-(5-t-butyl-4-hydroxy-m-tolyl)propionate, tris(2,4-di-t-butylphenyl)phosphite, bis(2,4-di-t-butylphenyl)pentaerythritol diphosphite, etc. These may be used alone or in combination of two or more.
[0038] The above-mentioned phenol-based antioxidants function as radical traps that donate hydrogen to ROO· (peroxy radicals) generated during the chain growth process of autoxidation to stabilize them, and then become stable phenoxy radicals protected by ortho-position substituents to stop the chain reaction, thereby effectively suppressing thermal degradation of the resin composition. In particular, the phenol-based antioxidants are more effective when used in combination with lactone-based antioxidants or vitamin E-based antioxidants, which have a faster radical trapping reaction than phenol-based antioxidants. In addition, the above-mentioned phosphorus-based antioxidants function to non-radical decompose peroxides and ROOH and stop the chain reaction of the autoxidation process, thereby effectively suppressing thermal degradation of the resin composition.
[0039] The ultraviolet absorbing agent is not particularly limited, and examples thereof include commonly used ones such as salicylic acid type, benzophenone type, benzotriazole type, etc. These may be used alone or in combination of two or more types.
[0040] The light stabilizer may be a commonly used hindered amine type light stabilizer.
[0041] <Color-changing hot melt adhesive for attaching road marking materials> A color-changing hot melt adhesive for attaching road surface marking materials can be produced by blending a color former (E) and, if necessary, an acidic substance (F) with the hot melt adhesive for attaching road surface marking materials of the present application. In the hot melt adhesive for attaching color-changing road surface marking materials, the sum of the acid values of (A), (B), (C), and (D) is preferably 0.8 mgKOH / g or more, or the sum of the acid values of (A), (B), (C), (D), and (F) is preferably 0.8 mgKOH / g or more. By making the acid value 0.8 mgKOH / g or more, the color development at room temperature becomes good, and the heat-melted state can be visually confirmed. The acid value is a value measured by neutralization titration method in accordance with JIS K-0070. Details are described in the Examples section.
[0042] The color former (E) is preferably a color former having a lactone structure, which, when used in combination with an acid, solidifies at room temperature and develops color. By adjusting the amount of acid, the color can be removed by heating until melted. Any of the following can be used: 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide, 3,6-bis(diethylamino)fluoran-γ-(4'-nitro)-anilinolactam, 2-N,N-dibenzylamino-6-diethylaminofluoran, N,N-dimethyl-4-(2-(octyloxy)phenyl)-6-phenylpyridin-4-yl)-benzeneamine. The color former (E) is preferably 0.01 to 3 mass% or less relative to 100 mass% of the hot melt adhesive for attaching road surface marking materials. When the color-changing hot melt adhesive for attaching road surface marking materials is heated to 120° C. or higher, the change from colored to colorless or from colored to a different color can be visually confirmed in a short time.
[0043] <Acidic substances (F)> The acidic substance (F) is appropriately mixed so that the total acid value of (A), (B), (C), (D) and (F) is 0.8 mgKOH / g or more. Examples of the acidic substance (F) that can be used include organic acids such as citric acid, succinic acid, gluconic acid, lactic acid, fumaric acid, malic acid, oxalic acid, acetic acid, formic acid, and uric acid, acid anhydrides such as acetic anhydride, hydrochloric acid, sulfuric acid, phosphoric acid, and nitric acid. EXAMPLES
[0044] The present invention will be described in more detail below with reference to examples. However, the present invention is not limited to these examples. In the examples, "parts" means "parts by mass," "%" means "% by mass," and blank spaces mean that no compound is included. The softening points and acid values of the materials used were measured as follows.
[0045] <Softening point> The softening point was measured by the ring and ball method in accordance with JIS K6863-1994, using an automatic ring and ball softening point tester ASP-MG4 manufactured by Meitec Corporation.
[0046] <Acid value> The acid value was measured by neutralization titration in accordance with JIS K-0070. Specifically, the sample was dissolved in a solvent, phenolphthalein was added as an indicator, and the acid value was determined by titration with an ethanol solution of potassium hydroxide.
[0047] <Manufacture of hot melt adhesives for attaching road marking materials> [Example 1] Crystallex 5140 (20 parts) and Haritac PH (30 parts) were weighed out and placed in a beaker equipped with a stirrer, and the materials were heated to melt and mixed using a mantle heater so that the temperature did not exceed 170° C. Clarity LA2250 (50 parts) was gradually added thereto, dissolved, and then mixed under reduced pressure to obtain the hot melt adhesive for attaching road surface marking materials of Example 1.
[0048] [Examples 2 to 23, Comparative Examples 1 to 8] According to the compositions in Tables 1 and 2, and in the same manner as in Example 1, hot melt adhesives for attaching road surface marking materials of Examples 2 to 23 and Comparative Examples 1 to 8 were obtained.
[0049] <Manufacture of color-changing hot melt adhesive for attaching road marking materials> [Example 24] Crystallex 5140 (25 parts), Haritac PH (13 parts), and Adeka STAB FP600 (25 parts) were weighed out and placed in a beaker equipped with a stirrer, and the materials were heated and dissolved in a mantle heater so that the temperature did not exceed 170° C., and mixed. Then, Clarity LA2250 (50 parts) weighed out was gradually added and dissolved, and then citric acid (0.5 parts) was added, and finally 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide (0.01 parts) was added and mixed under reduced pressure to obtain the color-changing hot melt adhesive for attaching road surface marking materials of Example 24.
[0050] [Examples 25 to 27, Comparative Examples 9 to 11] According to the compositions in Table 3, and in the same manner as in Example 22, color-changing hot melt adhesives for attaching road surface marking materials of Examples 23 to 26 and Comparative Examples 9 to 11 were obtained.
[0051] <Production of hot melt adhesive containing synthetic wax (G) for attaching road marking materials> [Example 29] Crystallex 5140 (17 parts), Haritac PH (10 parts), Crystallex F100 (7 parts), and Adeka STAB FP600 (11 parts) were weighed out and placed in a beaker equipped with a stirrer, and the materials were heated to melt and mixed using a mantle heater so that the temperature did not exceed 170° C. Then, Clarity LA2250 (55 parts) was gradually added and dissolved, and then ITOWAX J420 (10 parts) was added and mixed under reduced pressure to obtain the color-changing hot melt adhesive for attaching road surface marking materials of Example 29.
[0052] [Examples 30 to 35] According to the compositions in Table 4, and in the same manner as in Example 29, hot melt adhesives for attaching road surface marking materials of Examples 30 to 35 were obtained.
[0053] The abbreviations used in Tables 1 to 4 are as follows. [Block copolymer (A)] (A1) Triblock copolymer of methyl methacrylate and n-butyl acrylate with a mass ratio of methyl methacrylate of 30 mass% (manufactured by Kuraray, product name: Clarity LA2250, no acid value) (A2) Triblock copolymer of methyl methacrylate and n-butyl acrylate with a mass ratio of methyl methacrylate of 20 mass% (manufactured by Kuraray, product name: Clarity LA2140E, no acid value) (A3) Triblock copolymer of methyl methacrylate and n-butyl acrylate with a mass ratio of methyl methacrylate of 15 mass% (manufactured by Kuraray, product name: Clarity LA3320, no acid value) (A4) Triblock copolymer of methyl methacrylate with a mass ratio of methyl methacrylate of 17% by mass and a mixture of n-butyl acrylate / 2-ethylhexyl acrylate (manufactured by Kuraray Co., Ltd., product name: Clarity LK9243, no acid value) (A5) Triblock copolymer of methyl methacrylate and n-butyl acrylate with a mass ratio of methyl methacrylate of 10 mass% (manufactured by Kuraray Co., Ltd., product name: Clarity LA2114, viscosity at 190°C: 1700 mPa s, no acid value) (A6) Triblock copolymer of methyl methacrylate and n-butyl acrylate with a mass ratio of methyl methacrylate of 52 mass% (manufactured by Kuraray, product name: Clarity LA1892, no acid value) [Other Copolymers (X)] (X1) Polymethyl methacrylate (manufactured by Mitsubishi Chemical Corporation, product name: ACRYPET SV001, no acid value) (X2) Ethylene vinyl acetate copolymer (manufactured by Tosoh, product name: Ultrathene 720, vinyl acetate content 28%, no acid value) (X3) A hard segment-soft segment-hard segment triblock copolymer consisting of a styrene hard segment with a styrene ratio of 19% by mass and an isoprene soft segment (manufactured by Kraton, product name: Kraton D-1160, no acid value) [Tackifier (B)] (B1) Polymerized rosin (manufactured by Arakawa Chemical Industries, Ltd., product name: Pine Crystal KR140, softening point 140°C, acid value 145mgKOH / g) (B2) α-methylstyrene resin (manufactured by Eastman Chemical Company, product name: Crystallex 5140, softening point 140°C, no acid value) (B3) Terpene phenol resin (manufactured by Yasuhara Chemical Co., Ltd., product name: YS Polystar T130, softening point 130°C, no acid value) (B4) Copolymer of aromatic monomers (manufactured by Eastman Chemical Company, product name: Endex 155, softening point 155°C, no acid value) [Tackifier (C)] (C1) Hydrogenated rosin ester (Harima Chemicals, product name: Haritac PH, softening point 97°C, acid value 16mgKOH / g) (C2) Hydrogenated rosin (manufactured by Nissei Rinsan Kako Co., Ltd., product name: RHR-301, softening point 80°C, acid value 170mgKOH / g) (C3) Modified rosin (Harima Corporation, product name: Haritac KF125, softening point 125°C, acid value 18mgKOH / g) (C4) Rosin ester (manufactured by Arakawa Chemical Industries, Ltd., product name: Pencel GA100, softening point 100°C, acid value 18mgKOH / g) (C5) α-methylstyrene resin (manufactured by Eastman Chemical Company, product name: Crystallex F100, softening point 100°C, no acid value) (C6) α-methylstyrene resin (manufactured by Eastman Chemical Company, product name: Crystallex 3085, softening point 85°C, no acid value) (C7) Petroleum-based tackifier, aliphatic hydrocarbon resin (manufactured by Zeon Corporation, product name: Quinton A100, softening point 100°C, no acid value) (C8) Petroleum-based tackifier, aliphatic / aromatic copolymer (manufactured by Zeon Corporation, product name: Quinton G115, softening point 115°C, no acid value) (C9) Terpene phenol resin (manufactured by Yasuhara Chemical Co., Ltd., product name: YS Polystar T115, softening point 112°C, no acid value) [Plasticizer (D)] (D1) Phosphate ester (manufactured by Adeka Corporation, product name: Adeka STAB FP600, acid value 0.1 mg KOH / g) (D2) Adipic acid polyester (manufactured by J-Plus, product name: D623, acid value 1.0 mg KOH / g) (D3) Phthalate ester (manufactured by J-Plus, product name: DOP, acid value 0.02 mg KOH / g) (D4) Epoxidized vegetable oil (manufactured by Adeka, product name: Adeka Cizer O-130P, acid value 0.3 mg KOH / g) (D5) Glycerol fatty acid ester (manufactured by Riken Vitamin Co., Ltd., product name: Rikemal PL012, acid value 3.0 mg KOH / g) [Color former (E)] (E1) 3,3-bis(p-dimethylaminophenyl)-6-dimethylaminophthalide (discolors blue in acidic conditions) [Acidic substances (F)] (F1) Citric acid [Synthetic wax (G)] (G1) N-hydroxyethyl-12-hydroxystearic acid amide (manufactured by Ito Oil Mills, product name: ITOWAX J420, melting point 105°C) (G2) N,N'-xylylene-bis-12-hydroxystearic acid amide (manufactured by Ito Oil Mills, product name: ITOWAX J700, melting point 125°C) (G3) Glyceryl monostearate (manufactured by Riken Vitamin Co., Ltd., product name: Rikemal S-100A, melting point 63-68) (G4) Glyceryl monolaurate (manufactured by Riken Vitamin Co., Ltd., product name: Rikemal M300, melting point approximately 57°C) [Other waxes (G')] (G'1) Carnauba wax (manufactured by Toyochem, melting point 80-86°C)
[0054] <Softening point> The softening point of the color-changing hot melt adhesive for attaching road surface marking materials was measured in accordance with JIS K6863-1994, specifically, using a ring and ball type automatic softening point tester ASP-MG4 manufactured by Meitec Corporation.
[0055] <Preparation of test specimen> [Examples 1 to 35, Comparative Examples 1 to 11] The obtained hot melt adhesive was made into a film with a thickness of 1 mm using a heat press at 150° C., and then cut into test pieces of 30 mm length x 30 mm width and 100 mm length x 100 mm width. <Evaluation of color change upon heating> A stainless steel plate was placed on a hot plate and the temperature was adjusted to 150° C. The test piece prepared above was placed on the stainless steel plate on the hot plate, and the color change before and after heating and melting was visually evaluated. ◯: The color change before and after heating and melting is immediately and clearly visible: Good △: Color change before and after heating and melting can be seen within 20 seconds: Practical ×: No color change is observed before and after heating and melting within 20 seconds, or no color is observed before heating: Not practical
[0056] <Evaluation of heat solubility> The test piece having a length of 30 mm and a width of 30 mm prepared above was placed on a hot plate adjusted to a temperature of 150° C. and left for 20 seconds, and dissolution was evaluated based on the change in the shape of the test piece. ◎: The test piece melted and expanded in shape within 5 seconds: Excellent ◯: The test piece dissolved and expanded in 5 to 10 seconds: Good △: The test piece dissolved and expanded in 10 to 20 seconds: usable ×: The test piece did not dissolve even after 20 seconds, and no change in shape was observed: Not practical
[0057] <Preparation of laminate for measuring adhesive strength> After applying an epoxy primer to the scraped surface of a JIS concrete slab and letting it harden, the 100mm x 100mm test piece prepared above was placed on it, heated with a dryer for 60 seconds, and then a polyvinyl chloride (PVC) sheet was attached by hand. The JIS concrete slab was a scraped product manufactured by TP Giken Co., Ltd. (300 x 300 x 60mm), and the PVC sheet was a commercially available 400μm PVC sheet cut to 100mm x 100mm.
[0058] <Initial adhesive strength evaluation> A copper probe measuring 40mm in length and 40mm in width, which is attached to a tensile tester, was attached to the PVC sheet of the laminated material using a commercially available quick-drying epoxy resin and left for 1 hour. A cut was made around the copper probe using a concrete cutter until it reached the concrete slab, and the shaft of the measuring part of the tensile tester was connected to the copper probe, and measurements were taken in an atmosphere of 23°C and 65% relative humidity. A simple tensile tester, Technotester RT-1000LD(II), manufactured by Sanko Techno Co., Ltd., was used to evaluate the adhesive strength. 〇: 2.0kN or more / (40mm×40mm): Good △: 1.5 to less than 2.0 kN / (40 mm x 40 mm): Practical ×: Less than 1.5kN / (40mm×40mm): Not practical
[0059] <-10℃ Adhesion strength evaluation> The same bonded specimen with the copper adhesive attached and the tester used in the above initial adhesive strength evaluation were used. The bonded specimen with the copper adhesive attached was kept in a freezer at -10°C for 2 hours, and then measurements were performed under the same conditions. 〇: 2.0kN or more / (40mm×40mm): Good △: 1.5 to less than 2.0 kN / (40 mm x 40 mm): Practical ×: Less than 1.5kN / (40mm×40mm): Not practical
[0060] <60℃ Adhesion strength evaluation> The same bonded specimen with the copper adhesive attached and the tester were used as in the above initial adhesive strength evaluation. The bonded specimen with the copper adhesive attached was kept in an oven at 60°C for 2 hours, and then measurements were performed under the same conditions. 〇: 1.0kN or more / (40mm×40mm): Good △: 0.5 to less than 1.0 kN / (40 mm x 40 mm): Practical ×: Less than 0.5kN / (40mm×40mm): Not practical
[0061] [Table 1]
[0062] [Table 2]
[0063] [Table 3]
[0064] [Table 4]
Claims
1. The present invention comprises a block copolymer (A) including a polymer block including a structural unit derived from an alkyl methacrylate ester having an alkyl group with 1 to 3 carbon atoms and a polymer block including a structural unit derived from an alkyl acrylate ester having an alkyl group with 1 to 8 carbon atoms, a tackifier (B) having a softening point of 130° C. or more, and a tackifier (C) having a softening point of less than 130° C., A hot melt adhesive for attaching road surface marking materials, having a softening point of 90°C or higher, comprising 40 to 70% by mass of a block copolymer (A) and 5 to 45% by mass of a tackifier (B) relative to a total of 100% by mass of (A), (B), and (C), and the total of the tackifier (B) and the tackifier (C) is 30 to 60% by mass.
2. 2. The hot melt adhesive for attaching road surface marking materials according to claim 1, further comprising a plasticizer (D) which is liquid at 23°C.
3. 2. The hot melt adhesive for attaching road surface marking materials according to claim 1, further comprising a synthetic wax (G).
4. 2. The hot melt adhesive for attaching road surface marking materials according to claim 1, wherein the mass ratio of the methacrylic acid alkyl ester having an alkyl group with 1 to 3 carbon atoms in the block polymer (A) is 10 to 55 mass %.
5. A color-changing hot melt adhesive for attaching road surface marking materials, comprising 0.003 to 3 mass % of a color former (E) relative to 100 mass % of the hot melt adhesive for attaching road surface marking materials according to any one of claims 1 to 4, and satisfying the following (1) or (2). (1) The sum of the acid values of (A), (B), (C), and (D) is 0.8 mg KOH / g or more. (2) Further containing an acidic substance (F), the sum of the acid values of (A), (B), (C), (D) and (F) is 0.8 mgKOH / g or more.
Citation Information
Patent Citations
Road surface indicating material and method for sticking road surface indicating material to road surface
JP2001026915A
Self-adhesive composition
JP2008106176A
Braille tile for visually-handicapped person
JP2012097561A
Luminescent road surface marking material, luminescent road surface marking sheet, and luminescent road surface marking construction method
JP2012202052A
Pressure-sensitive adhesive composition
JP2017203172A